Hubungan Pola Asuh Ibu dengan Pola Pemberian Makan pada Anak Stunting di Wilayah Kerja Puskesmas Sumberjambe Kabupaten Jember - Rahmawati, Ira; Septiyono, Eka Afdi; Dewi, Fitria (Pustaka Kesehatan, 2025)
One of the worldwide health concerns is nutrition. Parenting is the practice of childcare that occurs in the household through the provision of food, health care, and other resources for child survival, development, and growth. This study aims to analyze the relationship between maternal parenting and feeding patterns in stunted children in the Sumberjambe Health Center working area, Jember Regency. This study used a correlational design with a cross-sectional study design. The number of respondents was 94, who were recruited with a random sampling technique. Data were collected using a questionnaire. The maternal parenting variables mostly have good parenting patterns, majority in toddlers aged 13-36 months, with male gender, mostly are not working mothers, and majority age 21-35 years with 2 children, the last education is elementary school, the number of family members is 5 people, and feeding patterns mostly have inappropriate patterns. The correlation between maternal parenting and feeding patterns was statistically significant (p = 0.0001, r = -0.577). The results showed that there was a significant correlation between maternal parenting and feeding patterns. Therefore, further information and education regarding maternal parenting and feeding patterns in stunted children are needed to prevent stunting.